2017
DOI: 10.1007/s11103-017-0650-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of a p-coumaroyl CoA 2′-hydroxylase involved in the biosynthesis of coumarin skeleton from Peucedanum praeruptorum Dunn

Abstract: A p-coumaroyl CoA 2'-hydroxylase responsible for the formation of coumarin lactone ring was identified from Peucedanum praeruptorum Dunn and functionally characterized in vitro. Coumarins are important plant secondary metabolites with a variety of biological activities. Ortho-hydroxylation of cinnamates leads to the formation of coumarin lactone ring and is generally thought to be a key step in coumarin biosynthesis. However, ortho-hydroxylases, especially p-coumaroyl CoA 2'-hydroxylase (C2'H) responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The coumarin umbelliferone and the flavone luteolin are commonly occurring phenylpropanoid metabolites in members of the Apiaceae family and serve as a precursor for a range of specialized metabolites, including pyrano-coumarins and furano-coumarins (Luo et al 2017; Yao et al 2017). Therefore, we quantified umbelliferone and luteolin across the select plant organs (Supplementary Figure S7A and S7B) and isolated oleo-gum-resin fractions (Supplementary Figure S7C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coumarin umbelliferone and the flavone luteolin are commonly occurring phenylpropanoid metabolites in members of the Apiaceae family and serve as a precursor for a range of specialized metabolites, including pyrano-coumarins and furano-coumarins (Luo et al 2017; Yao et al 2017). Therefore, we quantified umbelliferone and luteolin across the select plant organs (Supplementary Figure S7A and S7B) and isolated oleo-gum-resin fractions (Supplementary Figure S7C).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a more expansive evolutionary divergence of this pathway component may have occurred in F. assafoetida . In contrast, only a single transcript was identified that showed significant similarity to p-coumaroyl-CoA 2′-hydroxylase (C2’H) enzymes that catalyze the hydroxylation of the 4CL product p-coumaroyl-CoA as a key reaction in the formation of coumarins such as umbelliferone (Yao et al 2017) (Figure 3). Unlike coumarins, biosynthesis of flavone metabolites, including luteolin abundant in F. assafoetida oleo-gum-resin and other organs (Figure S7), proceeds through the activity of a chalcone synthase (CHS), followed by further modifications by chalcone isomerases (CHI), flavone synthases (FNS), and flavanone 3-hydroxylases (F3′H) (Bourgaud et al 2006; Naoumkina et al 2010; Vogt 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the fragment was ligated into the expression vector pET28a for protein expression and purification. For COMT-S purification, 6× His purification label according to our previously report was used [26]. The protein was further purified via gel-filtration chromatography on a Superdex 200 column (GE Healthcare, Pittsburgh, PA, USA) equilibrated with running buffer (RB) (25 mM Tris-HCl pH 8.0, 150 mM NaCl).…”
Section: Methodsmentioning
confidence: 99%
“…flavonoids and stilbenoids, coumarins are not polyketides, as their lactone ring structure is derived from hydroxylation, isomerization, and lactonization of phenolic acids (cinnamic, p-coumaric, caffeic, or ferulic acid) or the corresponding phenolic acyl-CoA esters (Kai et al, 2008;Yao et al, 2017).…”
Section: B Box 1 Metabolites Of Mixed Biosynthetic Originmentioning
confidence: 99%